Connecting the self to traumatic and positive events: links to identity and well-being. Issue 10 (25th November 2016) - Merrill, Natalie; Waters, Theodore E. A.; Fivush, Robyn
ABSTRACT: Self-event connections in autobiographical narratives help integrate specific episodes from memory into the life story, which has implications for identity and well-being. Previous research has distinguished differential relations between positive and negative self-event connections to psychological well-being but less research has examined identity. In this study, examining self-event connections in emerging adults' narratives, 225 participants narrated a traumatic and an intensely positive experience and completed questionnaires assessing identity development and well-being. Participants who described more negative connections to self overall had higher psychological distress and identity distress, compared to those who described fewer negative connections. Participants who described positive connections to the self in traumatic events were more likely to have lower psychological distress, higher post-traumatic growth, and higher identity commitment, whereas positive connections in positive events was related to higher identity exploration and marginally higher post-traumatic growth. These findings contribute to a growing body of literature that suggests linking autobiographical memories to self can have differential effects on identity and well-being depending on the valence of the event and the connections made.